Factors affecting association between pain severity and physical activity among people with low back pain - Hellgren, Henri (My University, 2023)
Background The relationship between the intensity of physical activity and the severity of low back pain has widely been studied showing inconsistent results. Some previous research has been unable to detect such a relationship or reported a nonlinear association. It is possible that different groups of people might show dissimilar results concerning this association. It is unknown if such factors as age, sex, social status, educational level and overall disability may affect the correlation between physical activity and back pain Aim To detect factors, which may affect the relationship between PA and pain severity among patients with LBP. Design Cross-sectional survey-based study. Population 1,332 consecutive patients with low back pain visiting an outpatient university clinic. Methods Linear regression models were employed and models with significant interactions were analyzed graphically. Results Patients were 47.6 (15.0) years old and 64% were women. For the entire sample, LBP severity and the intensity of PA were negatively associated - the worse was LBP, the less was PA. Younger age, higher educational level, lower BMI and optimal perceived general health were associated with overall higher PA. For all these groups, the steepness of linear association between PA and LBP severity was similar. Moderate or severe disability showed a paradoxical inverse association – worsening disability was associated with increasing PA. Sex, smoking, marital status and occupation did not demonstrate significant interactions on the association between LBP and PA. Conclusion Several factors may significantly affect the mostly negative association between low back pain severity and physical activity: age, educational level, body weight, perceived general health, and disability severity. Younger age, higher educational level, normal weight and optimal perceived general health predicted overall higher physical activity. Sex, smoking, marital status and occupation did not show significant effects on the association between pain and physical activity. The severity of disability showed paradoxical effect on the relationship between pain and physical activity – severe disability was associated with increase in physical activity. Clinical rehabilitation impact Identifying factors – age, educational level, body weight, perceived general health, and disability severity – that may affect the association between back pain and physical may help to allocate preventive and rehabilitation resources with better effectiveness to groups which may benefit from interventions the most.
Keywords: Low Back Pain, Exercise, Sedentary Behavior, Disability Evaluation, Health Risk Behaviors